Acupuncture for amnestic mild cognitive impairment: A pilot multicenter, randomized, parallel controlled trial. Issue 46 (19th November 2021) - Zhang, Jiayu; Kuang, Xu; Tang, Chunzhi; Xu, Nenggui; Xiao, Songhua; Xiao, Lingjun; Wang, Shengwen; Dong, Yu; Lu, Liming; Zhang, Liang
Abstract: Introduction: Patients with amnesic mild cognitive impairment (aMCI) are more likely to develop Alzheimer disease than corresponding age normal population. Because Alzheimer disease is irreversible, early intervention for aMCI patients seems important and urgent. We have designed a pilot multicenter, randomized, parallel controlled trial to assess the efficacy and safety of acupuncture on aMCI, explore the feasibility of acupuncture in the treatment of aMCI, so as to provide a reference for large-sample clinical trials in the next stage. Method: We designed a pilot multicenter, randomized, parallel controlled trial. This trial aims to test the feasibility of carrying out a large-sample clinical trial. In this trial, 50 eligible patients with aMCI will be included and allocated to acupuncture group (n = 25) or sham acupuncture group (n = 25) at random. Subjects will accept treatment 2 times a week for 12 weeks continuously, with a total of 24 treatment sessions. We will select 6 acupoints (GV20, GV14, bilateral BL18, bilateral BL23). For the clinical outcomes, the primary outcome is Montreal cognitive assessment, which will be assessed from baseline to the end of this trial. And the secondary outcomes are Mini-mental State Examination, Delayed Story Recall, Clinical Dementia Rating scale, Global Deterioration Scale, Activity of Daily Life, Alzheimer Disease Assessment Scale-Cognitive Section, brain magnetic resonance imaging, brain functional magnetic resonance imaging, and event-related potential P300, which will be assessed before and after treatment. In addition, we will assess the safety outcomes from baseline to the end of this trial and feasibility outcome after treatment. We will evaluate neuropsychological assessment scale (Montreal cognitive assessment, Mini-mental State Examination, Alzheimer Disease Assessment Scale-Cognitive Section) at 3 months and 6 months after treatment. Discussion: This pilot trial aims to explore the feasibility of the trial, verify essential information of its efficacy and safety. This pilot study will provide a preliminary basis for carrying out a larger clinical trial of acupuncture on aMCI in near future.